Using the Amplitude of Pulse-Synchronous Intramuscular Pressure Oscillations When Diagnosing Chronic Anterior Compartment Syndrome. Issue 11 (11th November 2014) - Nilsson, Andreas; Zhang, Qiuxia; Styf, Jorma
Background: To diagnose chronic anterior compartment syndrome (CACS) among patients with exercise-induced leg pain, intramuscular pressure (IMP) is regarded as the gold standard. Two recent studies have suggested that the evidence for commonly used IMP criteria are weak, and the validity has therefore come under question. Purpose: To evaluate whether the amplitude of pulse-synchronous IMP oscillations at rest after an exercise test is a reliable parameter that may aid in diagnosing CACS. Study Design: Cohort study (diagnosis); Level of evidence, 2. Methods: A total of 89 consecutive patients with suspected CACS (mean age, 31 years) and 19 healthy subjects (mean age, 28 years) participated in this study. All participants performed an exercise test until they were unable to continue because of leg pain and/or muscle fatigue. The IMP was recorded continuously in the anterior compartment of the leg with a noninfusion pressure recording system, starting 15 to 30 seconds after discontinuation of exercise. To test the amplitude of pulse-synchronous IMP oscillations as an indicator of CACS, a peak-to-peak amplitude of >2 mm Hg was chosen as the cutoff value. The clinical diagnosis of CACS was considered reference standard. Results: The mean ± SD IMP 1 minute after exercise was 54 ± 16 mm Hg in 53 patients with CACS, 17 ± 6 mm Hg in 36 non-CACS patients, and 18 ± 5 mm Hg in control subjects. The mean amplitude of the oscillations was 7.1 ± 3 mm Hg in patients with CACS, 1.3 ± 0.9 mm Hg in non-CACS patients, and 1.5 ± 0.6 mm Hg in control subjects 1 minute after exercise. The sensitivity of the amplitude to validate CACS was 96%, while the specificity was 94%. The positive predictive value was 96%, and the negative predictive value was 94%. Conclusion: The amplitude of the pulse-synchronous IMP oscillations at rest after an exercise test that elicits a patient's leg pain and muscle fatigue has high sensitivity to identify an abnormally elevated IMP. Clinical Relevance: Oscillations are easily recorded during clinical routine IMP measurements. They ascertain the diagnosis of CACS, corroborate the level of IMP, and ensure catheter patency.